Review of sustainable construction practices in Malaysian construction industry - Hamza Momade, Mohammed; Mohd Rosli Hainin, Prof (International Journal of Engineering and Technology, 2018)
Three key principles of sustainable development which needs to be covered during construction works are social, economic and envi-ronmental. This paper outlines the holistic approach which must be taken to define the best practice throughout the lifecycle of a constructed building for responsible use of resources and energy. It also highlights on the driving forces behind the implementation of sustainable methods in construction and outlines the key elements involved in measuring how sustainable a building is designed to be. The research methodology is based on data collection via questionnaires and also adds the views from previous researchers on this topic. This paperâ€™s aim is to evaluate and enhance the current practice of sustainability in construction and what steps can be taken to enforce the construction teams to switch from the conventional methods to a sustainable method. . The seven strategies suggested includes education and awareness, effective management of natural resources and the environment, integrated development planning and implementations, prevention and control of pollution and environmental degradation, strengthening administrative and institutional mechanisms, proactive approach to regional and global environmental issues, and formulation and implementation of actions plans. The idea of stage by stage implementation shows that it is possible to implement sustainable methods during construction and a further review should be taken by the stakeholders to work on the idea and turn it into a reality.Â Â